Isolation and characterization of canine placenta‐derived mesenchymal stromal cells for the treatment of neurological disorders in dogs. Issue 1 (17th July 2017) - Long, Connor; Lankford, Lee; Kumar, Priyadarsini; Grahn, Robert; Borjesson, Dori L.; Farmer, Diana; Wang, Aijun
Abstract: Spinal cord injury (SCI) is a devastating disorder that affects humans and dogs. The prognosis of SCI depends on the severity of the injury and can include varying levels of motor and sensory deficits including devastating paraplegia and quadriplegia. Placental mesenchymal stromal cells (PMSCs) have been shown to improve wound healing and possess neuroprotective and immunomodulatory capabilities, but have not yet been clinically tested for the treatment of SCI. This study established a protocol to isolate fetal PMSCs from canine placentas and characterized their paracrine secretion profile and ability to stimulate neurons in vitro to assess their potential as a treatment option for neurological disorders in dogs. Canine PMSCs (cPMSCs) were plastic adherent and capable of trilineage differentiation. cPMSCs expressed typical MSC markers and did not express hematopoietic or endothelial cell markers. Genotyping of cPMSCs revealed fetal rather than maternal origin of the cells. cPMSCs were viable and mitotically expansive in a collagen hydrogel delivery vehicle, and they secreted the immunomodulatory and neurotrophic paracrine factors interleukin (IL)‐6, IL‐8, monocyte chemoattractant protein 1 (MCP‐1), and vascular endothelial growth factor (VEGF). cPMSCs also stimulated the growth of complex neural networks when co‐cultured with SH‐SY5Y cells, a neuroblastoma cell line used to model neuron growth in vitro. cPMSCs are analogous to human PMSCs. They meet the criteria to be defined as MSCs and represent a potential regenerative therapy option for neurological disorders in dogs with their robust growth in collagen hydrogel, stimulation of neural network formation, and secretion of potent paracrine factors. © 2017 International Society for Advancement of Cytometry